Prevalence of lower extremity peripheral arterial disease in individuals with chronic immune mediated inflammatory disorders. Issue 1 (September 2015) - Agüero, Fernando; González-Zobl, Griselda; Baena-Díez, Jose M.; Dégano, Irene R.; Garcia-Gil, Maria; Alzamora, María Teresa; Marrugat, Jaume; Comas-Cufí, Marc; Pera, Guillem; Elosua, Roberto; Ramos, Rafel; Grau, María
Abstract: Objective: To compare the prevalence of lower extremity peripheral artery disease (PAD) and to assess whether age-associated progression in ankle-brachial index (ABI) differs between individuals with chronic immune-mediated inflammatory diseases (CIID) and the general population. Methods: Pooled analysis with data from individuals aged 50 years and older with ABI measurements, obtained from population-based cross-sectional studies conducted in Catalonia (Spain). Information on three CIID diagnoses (i.e., inflammatory bowel disease, systemic connective tissue disorders, and inflammatory polyarthropathies and spondylopathies, considered as one entity for purposes of analysis) was obtained from electronic medical records. To ascertain the statistical association between PAD and CIID, logistic regression models were fitted and adjusted for age, sex, and cardiovascular risk factors. We tested the interaction between age and CIID diagnosis for ABI values. Results: We included 8799 individuals, 312 (3.6%) with CIID. The age-standardized prevalence of PAD was higher in the CIID group (12% vs. 6% in general population, p = 0.001), and the model adjusted for age, sex, and cardiovascular risk factors also showed higher risk in individuals with CIID [Odds Ratio (95% confidence interval) = 1.65 (1.15–2.38); p = 0.007]. The inflammatory polyarthropathies/spondylopathies diagnosis was significantly associated with PAD in the fully adjusted model [1.80 (1.18–2.75); p = 0.006]. The atherosclerotic process was accelerated in individuals with CIID, compared to the general population (p for interaction < 0.001). Conclusion: In individuals with CIID, age-standardized prevalence of PAD was significantly higher than in the general population and the atherosclerotic process was accelerated. However, only inflammatory polyarthropathies/spondylopathies was associated with significant risk of PAD. Highlights: Age-associated increase in risk of PAD and lower ABI in patients with CIID. Inflammatory polyarthropathies/spondylopathies showed an additional risk of PAD. Individuals diagnosed with CIID may present an accelerated atherosclerotic process.